THE INFLUENCE OF LITERACY AND SERVICE QUALITY ON THE DECISION TO BECOME A SYARIAH STOCK INVESTOR AT MNC SECURITIES PONTIANAK - Manik, Ulina Maharani (Universitas Muhammadiyah Pontianak, 2024)
As a country with a majority Muslim population, Indonesia has great potential to advance Islamic economic activities including investing in the Sharia Capital Market. The presence of a Sharia-compliant financial market facilitates efficient resource mobilization and maximizes fund allocation, thereby increasing the role of financial intermediary institutions in investment activities. The purpose of this study is to determine the effect of literacy and service quality on the decision to become a Sharia Stock investor at MNC Sekuritas Pontianak. This study uses a quantitative approach using a method through a questionnaire technique to obtain primary data. Then the data is processed using Smart Partial Least Squares (PLS) software with 100 research samples. This study was conducted at MNC Securities KC. Pontianak, which is located at the Pontianak Mall Ruko Complex, Block C, No. 26, Jl. Teuku Umar, Darat Sekip, Pontianak, West Kalimantan, 78243. The results of the study show that the P Values of the Literacy variable is 0.000